This can be interpreted as a line in 2d space. There are an infinite number of solutions. More than likely your real question is: "How can 27y + 18x = 21 be written in standard slope-intercept form?"
Same as 9y + 6x = 7 (divide both sides by 3).
Solve for y:
9y = 7 - 6x
y = (7 - 6x) / 9, or
y = (-2/3)x + 7/9
We now have an eaquation of a line: slope = -2/3, y-intercept = 7/9
Paste -2/3x + 7/9 into the calculator at http://www.coolmath.com/graphit/
and click "Eval" to visualize it.
Yx7y = 7y2 (squared )
3x - 9y = 27-9y = -3x + 279y = 3x - 27y = x/3 - 3The graph is a straight line, with (slope = 3), and passing through the point (y = - 3) on the y-axis.
5x - 2y = 4 [1] x + 5y = 0 [2] Substituting x into 1st equasion, by re-arranging 2nd: x + 5y = 0 x = -5y 5(-5y) - 2y = 4 -25y - 2y = 4 -27y = 4 y = -4/27 x = -5y x = -5(-4/27) x = 139/27 note: in most cases you will need to simplify the fraction. not in this case, this is an unlikely sum, usually given by an out of school tutor or there is an error with your reading of the question, usually the answers are better fractions.
y will be multiplied by 27. Remember, whatever you do to one side of an equation, you must do to the other. In this case, the relationship between x and y would be expressed as y = x^3 To triple x would look like y = (3x)^3 ...b/c you're tripling the value x alone, not the entire term x^3 y = 27x^3 ...after distributing the exponent (3^3 = 27) In order to set both sides of the equation equal, y must be multiplied by 27... 27y = 27x^3 TADA!
7 y - 4 + y + 5 = 287 y + y + 1 = 288 y + 1 = 288 y = 27y = 27/8y = 3.375
5*3y+1+12y-1 = 15y+1+12y-1 = 27y.
(y + 27)(y^2 - 27y + 729)
Since 27y is a factor of 54y3, it is automatically the GCF
35
Reorder the terms: -5 + 42y + 27y2 Factor a trinomial. (-5 + -3y)(1 + -9y)
Since 27y is a factor of 54y3, it is automatically the GCF.
Multiply first equation by 3 and second equation by 5:30x + 27y = 12, -30x + 20y = -25; add these two:47y = -13, making y = -13/47 and x = -61/94I have checked these values against the original equations and they satisfy both. Weird solution tho'!
189xy
If this was correctly written: Alternatively, you might have meant: 9x+2y=5 9x+2y=5y2x+3=0 2x+3y=09x+2y=5 27x+6y=152xy=-3 -4x-6x=09x+2y=5 23x=152x=-3/yx=15/239x+2y=52x+3/y=0 2(15/23)+3y=02(9x+2y)=(5) 30/23=-3y-9(2x+3/y)=0y=10/23, x= 15/2318x+4y=10-18x+-27/y=018x+4y=104y/y-10/y=27y/y-10=-31yy=10/319x+2(10/31)=59x=135/31x=.048, y=10/31
27
~(3)-27y=(36)/(1000)Reduce the expression (36)/(1000) by removing a factor of 4 from the numerator and denominator.~(3)-27y=(9)/(250)Since ~(3) does not contain the variable to solve for, move it to the right-hand side of the equation by subtracting ~(3) from both sides.-27y=-~(3)+(9)/(250)Divide each term in the equation by -27.-(27y)/(-27)=(-~(3)+(9)/(250))/(-27)Simplify the left-hand side of the equation by canceling the common terms.y=(-~(3)+(9)/(250))/(-27)Simplify the right-hand side of the equation by simplifying each term.y=(250~(3)-9)/(6750) y=0.06